Development of Patient Perspective Assessment Tool for Service Quality Assessment Based on Patients of Selected Public Hospitals Using Sem-Ann Hybrid Approach - Macatangay, John Russel L.; Associate Professor Francisco N. de los Reyes (2024)
Abstract

Public healthcare systems in the Philippines lack comprehensive and statistically validated service quality assessment tools to assess the hospital's current prioritization in improving service quality that they receive.

With this problem at hand, the author utilized existing research on frameworks that will assess the service quality of public hospitals using the perspective of the patients and statistically validated it using Structural Equation Modeling (SEM) and Artificial Neural Network (ANN) to develop a survey questionnaire. Out of all the service dimensions present in the modified framework, only affordability was deemed statistically insignificant based on the perspective of the patients. The developed assessment tool reflects the absence of affordability in its sections.
Includes reference
Thesis (Professional Master in Data Science (Analytics)---School of Statistics, University of the Philippines, Diliman. 2024
Keywords: Structural Equation Modeling -- Artificial Neural Network -- Public Hospitals -- Service Quality -- Assessment Tool